Hubungan karakteristik usia, jenis kelamin, dan status pernikahan terhadap kelelahan kerja perawat COVID-19 di RSUD Labuang Baji tahun 2021 - Dayat, La Ode Hidayat (Journal of Health Education and Literacy, 2023)
This research is motivated by the high rate of work fatigue of nurses on duty in hospital installations that serve COVID-19 patients, causing a decrease in efficiency and resilience at work. This study aims to determine the relationship between age, gender and marital status variables on the work fatigue of COVID-19 nurses at the Labuang Baji Regional General Hospital in 2021. The population of this study was the Covid-19 nurses at the Labuang Baji Hospital, totaling 72 people. This study is a quantitative study with a cross sectional design using a sampling method, namely simple random sampling and using the Chi-square test. The results of this study indicate that there is a relationship between age and work fatigue of the COVID-19 task force nurses with a value (p = 0.000 by showing p < 0.05), there is a relationship between gender and work fatigue of the Covid-19 task force nurse with a value of ( p = 0.029 by showing p < 0.05), there is a relationship between marital status and work fatigue of the Covid-19 task force nurse with a value (p = 0.000 by showing p < 0.05). This study suggests that hospitals pay attention to factors that can put pressure on nurses' work fatigue and Burnout Syndrome to all hospital employees who feel the impact and deal directly with cases of covid-19, both medical and non-medical personnel in the hospital.